ARDS associated with pneumonia caused by avian influenza A H7N9 virus treated with extracorporeal membrane oxygenation. (21st May 2014) - Tang, Xiao; He, Hangyong; Sun, Bing; Wan, Jun; Ban, Chengjun; Zhang, Chunyan; Wang, Shuqin; Xia, Jingen; Li, Jie; Liu, Yingmei; Cao, Bin; Tong, Zhaohui
Abstract This is a sporadic H7N9 avian influenza case that was the first severe imported case in Beijing and the first case of Hebei province in China. A 61‐year‐old female who had rapidly progressive pneumonia with respiratory distress and bilateral exduation and consolidation changes on chest X‐ray and computerized tomography (CT) scan that did not respond to ordinary antibiotics was diagnosed with influenza A (H7N9) infection in our hospital on July 19, 2013. Intravenous peramivir, veno‐venous extracorporeal membrane oxygenation (VV‐ECMO) and continuous veno‐venous hemofiltration were given on the same day of lab diagnosis because of severe acute respiratory distress syndrome and acute renal failure. With antimicrobial therapy and other supportive treatment, clinical symptoms and oxygenation of the patient improved gradually. VV‐ECMO was successfully removed on the 13th day. The testing for influenza A (H7N9) turned negative on day 16 since the antivirus therapy. Twenty‐three days after hospitalization, blood stream infection with multidrug‐resistant Acinetobacter Baumannii occurred, which lead to septic shock and death. Whether or not the influenza season in north China, the influenza screening should be carried out as a conventional test for the patients who are suspected of viral pneumonia. For the patients who need mechanical ventilation and ECMO support, the lung protective strategy under the guidance of transpulmonary pressure may be helpful for recovering the lung.